The long-term learning curve of holmium laser enucleation of the prostate (HoLEP) in the en-bloc technique: a single surgeon series of 500 consecutive cases - Wenk, Maren; Hartung, Friedrich; Egen, Luisa; Netsch, Christopher; Kosiba, Marina; Grüne, Britta; Herrmann, Jonas (World journal of urology, 2024)
Purpose  To evaluate perioperative parameters, clinical outcomes, and the learning curve of holmium laser enucleation of the prostate (HoLEP) of a single surgeon in 500 consecutive cases. - Methods  Demographic parameters, outcomes, and adverse events were evaluated. The learning curve for HoLEP in en-bloc technique of the first 500 consecutive patients was analyzed in clusters of 100 (clusters 1-5) using the Wilcoxen rank test, Chi² test and Kruskal Wallis test. - Results  Enucleation weight was similar in the clusters 1,2,3, and 5 (62 g, 63 g, 61 g, 61 g), in cluster 4 it was slightly higher at 73 g. There was a significant reduction in operating time from 67 min (cluster 1) to 57 min (cluster 2), 46 min (cluster 3), 53 min (cluster 4), and 43 min (cluster 5), p < 0.001. Enucleation efficiency (g/min) showed a steady increase (1.72, 2.24, 2.79, 2.92 vs. 2.99, p < 0.001). Laser energy efficiency also improved (2.17 vs. 2.12 vs. 1.71 vs. 1.65 vs. 1.55; p < 0.001). There was no measurable learning curve regarding the length of hospital stay (mean 2.5 days), catheterization time (1.9 days), hemoglobin drop (approx. 1 g/dl) or complications (p > 0.1). - Conclusions  HoLEP using the en-bloc technique is a safe and highly effective method. Over time, a slight but steady learning curve and improvement in operation time, enucleation efficiency and laser energy efficiency were shown even for an experienced surgeon - after 500 cases, still no plateau was reached. There was no measurable learning curve regarding blood loss, complications, length of hospital stay, and catheterization time.